Imaging and Purchasing Decision in Traditional Art Market - Gama, Agus Wahyudi Salasa; Rustiarini, Ni Wayan; Anggraini, Ni Putu Nita (International Research Journal of Management, IT & Social Sciences, 2018)
Art market or souvenir market can not be separated from the existence of Bali island, unlike a tourist destination. The development of modern souvenir market was very disturbing traders in the traditional souvenir market. Due to it was feared will turn off the traditional art market. In this regard, to ensure the factors that need to be optimized in order to increase tourist visits to traditional Art Market was very important to conduct research. Based on the background and the problem, this research has a purpose to analyze the influence of art market attribute, promotion and service quality to market image and purchasing decision with research location at Guwang Art Market. The present research was designed as a descriptive and analytic approach. It defined that was descriptive facts, followed by analysis of the significance of empirical facts found. The descriptions were included the facts of market attributes, promotion, service quality, and market image in purchasing decisions. The population in the study were tourists who visit Guwang Art Market. Data collection was conducted with questionnaires distributed to travelers visiting the Guwang Art Market in April-July 2015. Data analysis used Structural Equation Model.